A design methodology for acoustic resonance-free, high-frequency, dimmable electronic ballast for high-pressure sodium-vapour lamps. (June 2020) - Gupta Bakshi, B; Roy, B
This paper presents a methodology to design acoustic resonance-free, high-frequency, dimmable electronic ballasts for high-pressure sodium vapour (HPSV) lamps having a range of rated wattage (70–400 W). After estimation of the 'quiet window' of an HPSV lamp, the proposed iterative algorithm is able to determine the acoustic resonance-free driving frequencies of a design ballast corresponding to 50%–100% power level. On the other hand, a developed wattage and voltage independent HPSV lamp model facilitates finding the required electrical characteristics of HPSV lamps without performing laboratory experimentation. Using the estimated driving frequencies of a design ballast and the synthesized electrical characteristics of the lamp, the design circuit parameters of an electronic ballast are determined. Performance evaluation of the designed ballasts, carried out on the Matlab–Simulink platform, indicates several important attributes, viz. higher power control accuracy (deviation ≤3.69%), near-unity lamp power factor (≥0.98), lower lamp current crest factor (<1.7) and lower lamp current total harmonic distortion (≤12.63%). Results establish the effectiveness of the proposed design methodology to design lightweight and compact electronic ballasts for HPSV lamps with less effort than conventional design practice.